First-Line Sofia Aspiration Thrombectomy Approach within the Endovascular Treatment of Ischemic Stroke Multicentric Registry: Efficacy, Safety, and Predictive Factors of Success - Marnat, G.; Barreau, X.; Detraz, L.; Bourcier, R.; Gory, B.; Sgreccia, A.; Gariel, F.; Berge, J.; Menegon, P.; Kyheng, M.; Labreuche, J.; Consoli, A.; et al. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: After publications on the effectiveness of mechanical thrombectomy by stent retrievers in acute ischemic stroke with large-vessel occlusion, alternative endovascular approaches have been proposed using first-line aspiration catheters. Several devices are currently available to perform A Direct Aspiration First Pass Technique. The Sofia catheter aspiration has been widely used by interventionalists, but data are scarce about its efficacy and safety. Our aim was to report our multicenter thrombectomy experience with first-line Sofia catheter aspiration and to identify independent prognostic factors of clinical and procedural outcomes.MATERIALS AND METHODS: We performed a retrospective analysis of the prospectively maintained Endovascular Treatment of Ischemic Stroke multicentric registry. Data from consecutive patients who benefited from thrombectomy with a first-line Sofia approach between January 2013 and April 2018 were studied. We excluded other first-line approaches (stent retriever or combined aspiration and stent retriever) and extracranial occlusions. Baseline characteristics, procedural data, and angiographic and clinical outcomes were analyzed.RESULTS: During the study period, 296 patients were treated. Mean age and initial NIHSS score were, respectively, 69.5 years and 16. Successful reperfusion, defined by the modified TICI 2b/3, was obtained in 86.1% (n = 255; 95% CI, 81.7%–89.9%). Complete reperfusion (modified TICI 3) was obtained in 41.2% (n = 122; 95% CI, 35.5%–47.1%). A first-pass effect was achieved in 24.2% (n = 71; 95% CI, 19.4%–29.6%). A rescue stent retriever approach was required in 29.7% (n = 88; 95% CI, 24.6%–35.3%). The complication rate was 9.5% (n = 28; 95% CI, 6.4%–13.5%). Forty-three percent (n = 122; 95% CI, 37.1%–48.9%) of patients presented with a favorable 3-month outcome (mRS ≤ 2). Older age, M1-occlusion topography, and intravenous thrombolysis use prior to thrombectomy were independent predictors of the first-pass effect.CONCLUSIONS: The first-line contact aspiration approach appeared safe and efficient with Sofia catheters. These devices achieved very high reperfusion rates with a low requirement for stent retriever rescue therapy, especially for M1 occlusions.ADAPTA Direct Aspiration First Pass TechniqueDACdistal aspiration catheterETISEndovascular Treatment of Ischemic StrokeFPEfirst-pass effectIQRinterquartile rangeIVTintravenous thrombolysismTICImodified TICIPHparenchymal hematoma